Friend or Foe? The Roles of Antioxidants in Acute Lung Injury - Yang Liu; Shujun Zhou; Du Xiang; Lingao Ju; Dexin Shen; Xinghuan Wang; Yanfeng Wang (Antioxidants, 2021)
Acute lung injury (ALI) is an acute hypoxic respiratory insufficiency caused by various intra- and extra-pulmonary injury factors. The oxidative stress caused by excessive reactive oxygen species (ROS) produced in the lungs plays an important role in the pathogenesis of ALI. ROS is a “double-edged sword”, which is widely involved in signal transduction and the life process of cells at a physiological concentration. However, excessive ROS can cause mitochondrial oxidative stress, leading to the occurrence of various diseases. It is well-known that antioxidants can alleviate ALI by scavenging ROS. Nevertheless, more and more studies found that antioxidants have no significant effect on severe organ injury, and may even aggravate organ injury and reduce the survival rate of patients. Our study introduces the application of antioxidants in ALI, and explore the mechanisms of antioxidants failure in various diseases including it.